The feelgood mutation in zebrafish dysregulates COPII-dependent secretion of select extracellular matrix proteins in skeletal morphogenesis - David B. Melville; Mercedes Montero-Balaguer; Daniel S. Levic; Kevin Bradley; Jeffrey R. Smith; Antonis K. Hatzopoulos; Ela W. Knapik (The Company of Biologists, 2011)
SUMMARY Craniofacial and skeletal dysmorphologies account for the majority of birth defects. A number of the disease phenotypes have been attributed to abnormal synthesis, maintenance and composition of extracellular matrix (ECM), yet the molecular and cellular mechanisms causing these ECM defects remain poorly understood. The zebrafish feelgood mutant manifests a severely malformed head skeleton and shortened body length due to defects in the maturation stage of chondrocyte development. In vivo analyses reveal a backlog of type II and type IV collagens in rough endoplasmic reticulum (ER) similar to those found in coat protein II complex (COPII)-deficient cells. The feelgood mutation hinders collagen deposition in the ECM, but trafficking of small cargos and other large ECM proteins such as laminin to the extracellular space is unaffected. We demonstrate that the zebrafish feelgood mutation causes a single amino acid substitution within the DNA-binding domain of transcription factor Creb3l2. We show that Creb3l2 selectively regulates the expression of genes encoding distinct COPII proteins (sec23a, sec23b and sec24d) but find no evidence for its regulation of sec24c expression. Moreover, we did not detect activation of ER stress response genes despite intracellular accumulation of collagen and prominent skeletal defects. Promoter trans-activation assays show that the Creb3l2 feelgood variant is a hypomorphic allele that retains approximately 50% of its transcriptional activity. Transgenic rescue experiments of the feelgood phenotype restore craniofacial development, illustrating that a precise level of Creb3l2 transcriptional activity is essential for skeletogenesis. Our results indicate that Creb3l2 modulates the availability of COPII machinery in a tissue- and cargo-specific manner. These findings could lead to a better understanding of the etiology of human craniofacial and skeletal birth defects as well as adult-onset diseases that are linked to dysregulated ECM deposition, such as arthritis, fibrosis or osteoporosis.